2004
DOI: 10.1111/j.0001-6349.2004.00344.x
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory labor analgesia: what does an obstetrician need to know?

Abstract: A simple statement that describes the degree of the patient's satisfaction with the pain relief from her labor epidural analgesia has often assessed the quality of labor analgesia as perceived by the patient. Many laboring parturients, midwives, obstetricians and anesthesiologists are increasingly concerned by the limitations of traditional epidural labor analgesia. In general, women dislike the inability to void, the often-dense motor block, the feeling of numbness of the lower body, the total lack of the urg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…In studies on animals, levobupivacaine, the S(–)‐enantiomer of racemic bupivacaine, has been found to be associated with lower risks of cardiovascular and central nervous system toxicity compared with racemic bupivacaine (14,15). The analgesic effect of levobupivacaine has been found to be equivalent to that of racemic bupivacaine in many clinical studies, including studies on epidural anesthesia for cesarean section and epidural and intrathecal labor analgesia (16–20). However, levobupivacaine has not been widely used in PCB.…”
mentioning
confidence: 99%
“…In studies on animals, levobupivacaine, the S(–)‐enantiomer of racemic bupivacaine, has been found to be associated with lower risks of cardiovascular and central nervous system toxicity compared with racemic bupivacaine (14,15). The analgesic effect of levobupivacaine has been found to be equivalent to that of racemic bupivacaine in many clinical studies, including studies on epidural anesthesia for cesarean section and epidural and intrathecal labor analgesia (16–20). However, levobupivacaine has not been widely used in PCB.…”
mentioning
confidence: 99%
“…Motor block was assessed using the modified Bromage score (1 = complete block, unable to move feet or knees; 6 = able to perform partial knee bend while standing). [ 17 18 19 20 ]…”
Section: Methodsmentioning
confidence: 99%
“…9 The hypotension is especially critical in a postpartum mother because the average estimated blood loss is 500 mL with a vaginal birth and 1000 mL with a cesarean section, which potentiates hypotension. 10,11 Research has suggested that multifaceted interventions involving patient assessments in various areas aid in the reduction of falls. 2 After an epidural, regional anesthesia that blocks nerve impulses from lower spinal segments needs to wear off for the patient to ambulate.…”
Section: Defining the Problemmentioning
confidence: 99%